2017
DOI: 10.1111/ecog.03148
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling biotic interactions, environmental filters, and dispersal limitation as drivers of species co‐occurrence

Abstract: A key focus in ecology is to search for community assembly rules. Here we compare two community modelling frameworks that integrate a combination of environmental and spatial data to identify positive and negative species associations from presenceabsence matrices, and incorporate an additional comparison using joint species distribution models (JSDM).The frameworks use a dichotomous logic tree that distinguishes dispersal limitation, environmental requirements, and interspecific interactions as causes of segr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
176
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 76 publications
3
176
0
2
Order By: Relevance
“…2.11.12). These two pairwise co‐occurrence tests performed better than other available pairwise co‐occurrence tests in a recent analysis (Lavender et al ). For the first two years of community data (third year co‐occurrence would be linked to subsequent turnover), we independently subjected control and herbivore exclusion plots to these pairwise co‐occurrence tests and collected the identities of pairs identified as significantly negatively co‐occurring (alpha = 0.1) as well as those identified as positively co‐occurring (alpha = 0.1).…”
Section: Methodsmentioning
confidence: 82%
“…2.11.12). These two pairwise co‐occurrence tests performed better than other available pairwise co‐occurrence tests in a recent analysis (Lavender et al ). For the first two years of community data (third year co‐occurrence would be linked to subsequent turnover), we independently subjected control and herbivore exclusion plots to these pairwise co‐occurrence tests and collected the identities of pairs identified as significantly negatively co‐occurring (alpha = 0.1) as well as those identified as positively co‐occurring (alpha = 0.1).…”
Section: Methodsmentioning
confidence: 82%
“…, D'Amen et al. , Hui and Richardson ). The drivers of differences in bird community turnover shown between catchments, for example, clearly warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that nitrifier communities were also more segregated than expected by chance and that AOA and Nitrospira were even more segregated across the farm than AOB and Nitrobacter . Significant patterns of segregation are commonly attributed to deterministic forces, such as competition, nonoverlapping niches or historical effects such dispersal limitation or evolutionary processes (D'Amen, Mod, Gotelli, & Guisan, ; Horner‐Devine et al., ). Both Nitrospira and AOA are known to be highly diverse functional groups that occur in a wide range of environments (Daims et al., ; Hatzenpichler, ; Pester et al., , ), and niche partitioning across or even within lineages has been demonstrated for both groups (Gruber‐Dorninger et al., ; Gubry‐Rangin et al., ).…”
Section: Discussionmentioning
confidence: 99%